2018
DOI: 10.1177/1071100718806479
|View full text |Cite
|
Sign up to set email alerts
|

Hindfoot Arthrodesis Screw Position and Trajectory Effect on Talus Subsidence When Performed With Total Ankle Arthroplasty

Abstract: Background: Total ankle arthroplasty (TAA) is increasingly being recognized as an effective surgical option for end-stage ankle arthritis. Associated hindfoot arthrodesis procedures are at times needed to correct malalignment or to address adjacent joint arthritis. Results following TAA and associated hindfoot arthrodesis have at times been underwhelming and the devascularization of the talar blood supply has been postulated as a potential cause. This study explored the association between hindfoot arthrodesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, the screws used during the fixation of the subtalar joint may cause a decrease in the blood flow to the talus, which may lead to the subsidence of the talar component. 28 Therefore, considering the mobility of the subtalar joint in our cases, we did not perform subtalar joint fixation, but performed a combined TAA. The most common reasons for revision TAA have been shown to be infection, aseptic loosening, and talar component subsidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the screws used during the fixation of the subtalar joint may cause a decrease in the blood flow to the talus, which may lead to the subsidence of the talar component. 28 Therefore, considering the mobility of the subtalar joint in our cases, we did not perform subtalar joint fixation, but performed a combined TAA. The most common reasons for revision TAA have been shown to be infection, aseptic loosening, and talar component subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…24 When concurrent subtalar OA exist, studies have reported its treatment with TAA alone because of its low rate of progression, 22 pantalar arthrodesis, 13 or TAA with subtalar arthrodesis. 19,28 In TAA with subtalar arthrodesis, Prissel et al 19 reported that it did not result in decreased survivorship at an early follow-up point. Conversely, Taylor et al 28 reported that the screws used during the fixation of the subtalar joint may cause a decrease in the blood flow to the talus, which may lead to the subsidence of the talar component, especially when screws are placed from a dorsal to a plantar approach.…”
Section: Introductionmentioning
confidence: 99%